2021
DOI: 10.1055/s-0041-1729485
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Transfusion-Transmitted Infections among Voluntary and Replacement Blood Donors at the Peshawar Regional Blood Centre, Khyber Pakhtunkhwa, Pakistan

Abstract: Introduction Blood transfusion is linked to several risks, most notably the transmission of transfusion-transmitted infections (TTIs), including hepatitis B virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), syphilis, and malaria. The risk posed by these blood-borne infectious agents is high in developing countries, including Pakistan. This fact stresses the need for regular surveillance of TTIs. Therefore, the present study was undertaken to assess the seroprevalence of TTIs at a region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 34 publications
5
16
2
Order By: Relevance
“…A vast majority (42.92%) of the blood donors in the present study were between 18 and 30 years. This finding was consistent with studies from Pakistan (45.6%), 9 Kenya (42.24%), 10 and Tanzania (44.7%). 11 The blood donors in the present study had their mean ages 10–15 years less than those observed in developed western countries.…”
Section: Discussionsupporting
confidence: 92%
“…A vast majority (42.92%) of the blood donors in the present study were between 18 and 30 years. This finding was consistent with studies from Pakistan (45.6%), 9 Kenya (42.24%), 10 and Tanzania (44.7%). 11 The blood donors in the present study had their mean ages 10–15 years less than those observed in developed western countries.…”
Section: Discussionsupporting
confidence: 92%
“…The last point is that people who donated more than five times have already been screened multiple times. Repeat blood donors are therefore less at risk than new donors who never go through the screening process Similar results confirm that first-time donors have higher hepatitis B infection rates compared to regular and repeat blood donors[27] [28]. HBs antigen prevalence and blood donation.…”
supporting
confidence: 61%
“…We attribute this to the increase in replacement donations to meet the demand for various blood components as there was no change in the testing methodology used for syphilis screening in blood donors. Replacement donors have been shown to have a higher prevalence of transfusion-transmitted infections [13] , [14] , [15] , [16] . A recent study reported a reactive rate of 0.8% for all infections among voluntary donors and 1.95% in replacement donors(p˂0.001) in their analysis of trends of seroprevalence over 10 years [25] .…”
Section: Discussionmentioning
confidence: 99%
“…In such a situation, when voluntary donations are less, blood centres have to turn to other sources such as family donors and replacement donors [9]. Replacement donors have shown a higher prevalence of transfusion-transmitted infections as reported in various studies [13][14][15][16]. Although many blood centres have a system in place to motivate doctors and staff during emergent demands, these too are limited given the scale of the pandemic.…”
Section: Introductionmentioning
confidence: 99%